LASER PROPHYLAXIS IN STICKLER SYNDROME: The Manchester Protocol. Issue 1 (January 2023) - Linton, Emma; Jalil, Assad; Sergouniotis, Panagiotis; Moussa, George; Black, Graeme; Charles, Stephen; Ivanova, Tsveta
Abstract : Individuals with Stickler syndrome are at increased risk of developing giant retinal tears and retinal detachments. Findings from 113 eyes (63 patients) show that 360° retinal laser prophylaxis can help reduce the risk of developing visual loss in Stickler syndrome. Abstract : Purpose: Patients with Stickler syndrome are at high risk of giant retinal tears (GRTs) and detachments. Vitreoretinal interventions can reduce this risk, but there is presently no consensus about the optimal prophylactic approach. The aim of our study was to determine whether 360° laser prophylaxis is a safe and effective procedure to prevent GRT detachments in patients with Stickler syndrome. Methods: Study subjects were recruited retrospectively through the databases of the vitreoretinal and ophthalmic genetic tertiary services in Manchester, United Kingdom. Clinical data were collected including on prophylactic intervention, the occurrence of retinal detachment, and the presence/type of retinal breaks. Results: One hundred thirteen eyes from 63 patients with Stickler syndrome were studied; 72.6% (82/113) of these eyes received 360° laser prophylaxis. Of these, 9% had a retinal detachment, but no GRTs occurred. Among the 27.4% (31/113) of eyes that had no prophylactic treatment, 23% suffered a retinal detachment and 42.9% of these were associated with a GRT. Conclusion: Patients who underwent laser prophylaxis had fewer retinal detachments and no GRTs during an average of 6.1 years of follow-up (median 5 years), suggesting that this is a safe and effective approach for individuals with Stickler syndrome.